2020
DOI: 10.1002/mgg3.1434
|View full text |Cite
|
Sign up to set email alerts
|

Two novel KCNA1 variants identified in two unrelated Chinese families affected by episodic ataxia type 1 and neurodevelopmental disorders

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…However, GoF variants causing neuronal hyperexcitability have been described in several K + channel-encoding genes, 20 and it has been suggested that faster action potential repolarization may lead to sodium channels repriming, 21 thereby increasing firing frequency and synchronization, hallmarks of neuronal hyperexcitability in the epileptic tissue. The marked anticonvulsant efficacy of the sodium-channel blocker carbamazepine observed in our patient and in Patient 1 of Yuan et al, 10 who also carried the same p. A261T KCNA1 variant, but not in those with loss-of-function mutations, appears to support such a hypothesis.…”
Section: Discussionsupporting
confidence: 71%
“…However, GoF variants causing neuronal hyperexcitability have been described in several K + channel-encoding genes, 20 and it has been suggested that faster action potential repolarization may lead to sodium channels repriming, 21 thereby increasing firing frequency and synchronization, hallmarks of neuronal hyperexcitability in the epileptic tissue. The marked anticonvulsant efficacy of the sodium-channel blocker carbamazepine observed in our patient and in Patient 1 of Yuan et al, 10 who also carried the same p. A261T KCNA1 variant, but not in those with loss-of-function mutations, appears to support such a hypothesis.…”
Section: Discussionsupporting
confidence: 71%
“…Epilepsy with or without developmental delay or permanent ataxia has also been frequently reported in the context of both EA1 [30][31][32][33][34][35]) and EA2 [36][37][38]. A severe form of Early Infantile Epileptic Encephalopathy (EIEE) is reported in some members of EA2 families with CACNA1A loss-of-function mutations [39][40][41].…”
Section: Ea1 and Ea2mentioning
confidence: 99%
“…Episodic ataxia type 1 (EA1) is rare genetic ataxia due to a mutation of the KCNA1 gene. [2][3][4][5] The KCNA1 gene encodes the 495 amino acid (aa) Kv1.1 voltage-gated potassium (Kv) channel subunit. The Kv1.1 plays a pivotal role in regulating neuronal excitability by controlling the action potential, repolarization, and firing properties.…”
mentioning
confidence: 99%
“…2 A variety of clinical manifestations like ataxia, seizure, neuromyotonia, myokymia, seizures, encephalopathy, chorea, cognitive deficit, asterixis, muscle weakness, hyperthermia, and hypomagnesemia were reported in KCNA1 gene mutation. [2][3][4][5] Identical twins with KCNA1 mutation can demonstrate a different degree of ataxic symptoms. Such a wide range of symptoms with the KCNA1 gene mutation reflects the ubiquitous presence the voltage-gated potassium channel in the human body and its important role in various physiological functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation